Penguatan Mental Mahasantri Al-Jamiah IAIN Curup Melalui Kuliah Tujuh Menit - Wirawan, Pandy Akbar; Alghazali, Reno Diqqi; Anrial, Anrial (Journal of Da'wah, 2023)
Kultum is an abbreviation of 'seven-minute lecture', this makes every lecture activity carried out for a relatively short duration considered a kultum. From a linguistic point of view, a lecture or cult is a story or verbal explanation to express a purpose. In this research, the author used a qualitative descriptive research type. Qualitative research is collecting data in a natural setting to interpret phenomena that occur where the researcher is the key instrument. The morning cult activities at Ma'had al-Jami'ah Iain Curup are carried out every day. With direction from the ustadz dan ustadzah, the students who have finished the morning prayer then continue reading the selected surahs that have been determined, then after the students have finished reciting the Koran, the students sit in neat rows to listen to the sermon that has been scheduled by the ustadz dan ustadzah, and when The kultum has begun, the mahasantri listens carefully. Then, in carrying out the dawn kultum method to strengthen the mentality of the ma'had al-jami'ah mahasantri, they use various methods that are from the Islamic perspective, namely the example method, the habituation method, the advice method, the story method, and the reward method. Supporting and inhibiting factors for the implementation of the Subuh Kultum method in strengthening the mentality of Ma'had al-Jami'ah Iain Curup mahasantri can be seen from internal factors, the Mahasantri can listen well to the Subuh Kultum material being delivered, while the inhibiting factors are that Mahasantri are late in attending the Subuh Kultum and are noisy. during the dawn cult. Meanwhile, for external factors, there is good cooperation between fellow ustadz dan ustadzah to bring order to mahasantri, the availability of adequate facilities and infrastructure for carrying out the dawn cult, and the allocation of time specifically for the dawn cult. Meanwhile, the inhibiting factor is that the mahasantri often stop delivering cult material in the middle because they feel disturbed by the noisy mahasantri